Building Vicarious Bridges through Colour Workshops for Pupils with Visual Impairment - Filomena Agrillo; Paola Aiello; Iolanda Zollo; Erika Marie Pace; Maurizio Sibilio (Athens Institute for Education and Research, 2017)
The inclusion of pupils with visual impairment, within Italian mainstream schools, is an area of interest for the field of special education that is involved in identifying the most effective teaching strategies to promote the teaching-learning process. The perceptive difficulties that the pupils with visual impairment encounter in the first step of development can be a significant obstacle to learning and to the development of representative thinking. For this reason, it is fundamental that the teaching style adopted is oriented to promote learning through strategies that exploit the natural vicarious activity of the brain. With this aim, the present paper describes the potential of a hands-on activity with high inclusive value, which is based on a theoretical framework, that brings together contributions from different scientific domains and which, from an interdisciplinary perspective, explores the concept of "vicariance" as proposed by the physiologist of perception Alain Berthoz.